Faktor yang Mempengaruhi Kinerja Keuangan Perbankan di Indonesia Dari Sisi Modal dan Ukuran Bank - Seflidiana Roza; Arfimasri Arfimasri; Chintia Aulia (Pusat Riset dan Inovasi Nasional, 2026)
The financial results of a bank serve as a crucial metric in evaluating how effectively management handles assets and ensures the company’s long-term viability. Internal factors such as the bank's capital structure and size are believed to impact its financial performance. This research aims to examine the effects of both the bank's capital structure and size on the financial outcomes of banking sector firms listed on the Indonesia Stock Exchange during the period from 2021 to 2024, looking at these influences both individually and collectively. A quantitative research approach is utilized, relying on secondary data derived from annual financial statements. The sample for this study consists of 41 companies, selected through a purposive sampling technique. The data analysis techniques used included multiple linear regression, determination coefficient (R²) test, and hypothesis test through t-test and F-test. Simultaneously, the capital structure and size of the bank have a significant effect on financial performance. A determination coefficient value (R²) of 0.163 indicates that the two independent variables are able to explain 16.3% of the variation in financial performance, while the rest is influenced by other factors outside the research model. The analytical methods employed comprised multiple linear regression, determination coefficient (R²) assessment, and hypothesis testing through t-tests and F-tests. At the same time, the structure of capital and the size of the bank significantly impact financial performance. An R² value of 0.163 suggests that the two independent variables account for 16.3% of the variance in financial performance, while the remaining variance is affected by factors not included in the research model.